Neuroproteomic study of nitrated proteins in moderate traumatic brain injured rats treated with gamma glutamyl cysteine ethyl ester administration post injury: Insight into the role of glutathione elevation in nitrosative stress. Issue 12 (11th November 2016) - Henderson, Moses; Rice, Brittany; Sebastian, Andrea; Sullivan, Patrick G.; King, Christina; Robinson, Renã A.S.; Reed, Tanea T.
Abstract : Purpose: The aims of this study are to establish a time point to determine the most beneficial time to administer GCEE post incident to reduce oxidative damage and second, by using redox proteomics, to determine if GCEE can readily suppress 3‐NT modification in TBI animals. Experimental design: By using a moderate traumatic brain injury model with Wistar rats, it is hypothesized that the role of 3‐nitrotyrosine (3‐NT) formation as an intermediate will predict the involvement of protein nitration/nitrosation and oxidative damage in the brain. Results: In this experiment, the levels of protein carbonyls, 4‐hydroxynonenal, and 3‐nitrotyrosine were significantly elevated in TBI injured, saline treated rats compared with those who sustained an injury and were treated with 150 mg/kg of the glutathione mimetic, GCEE. Conclusion and clinical relevance: Determining the existence of elevated 3‐NT levels provides insight into the relationship between the protein nitration/nitrosation and the oxidative damage, which can determine the pathogenesis and progression of specific neurological diseases.